2022
DOI: 10.1002/adma.202202180
|View full text |Cite
|
Sign up to set email alerts
|

Engineering DNA‐Guided Hydroxyapatite Bulk Materials with High Stiffness and Outstanding Antimicrobial Ability for Dental Inlay Applications

Abstract: However, due to the absence of long-range ordered structures in biological templates, the mechanical performance of synthetic HAP is markedly lower than that of natural bone or dentin. For example, the Young's modulus of HAP mineralized using bacterial cellulose is ≈10.9 GPa, which is significantly lower than that of human dentin (≈22.5 GPa). [11] The low mechanical stiffness and toughness of artificial HAP biomaterials limit their biomedical applications. Hence, it is important to develop novel biological tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…It was confirmed that pores have an essential role in moisture, gases, and drug transporting through wounds and the outer environment. Moreover, the porous surface might improve the mutual equilibrium between the mechanical and biological properties [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was confirmed that pores have an essential role in moisture, gases, and drug transporting through wounds and the outer environment. Moreover, the porous surface might improve the mutual equilibrium between the mechanical and biological properties [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in Figure 8 , the viable cells that were detected by the optical microscope were represented in the form of rod shapes with high distribution, while the dead cells were distributed with low concentration in the form of spherical shapes. In addition, the porous scaffold determined by SEM caused an increase in the cell viability value [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a vital component of teeth, natural hydroxyapatite (HAP) has great biological activity and osteoconductivity [106]. However, existing artificial HAP biomaterials suffer from low mechanical stiffness and toughness, limiting their application in the biomedical field.…”
Section: Templates For Biomedical Materialsmentioning
confidence: 99%
“…Inorganic shells were grown on DNA structures by precisely controlling the coating reaction parameters via the environmental changes , (e.g., pH and solvent) and precursor concentrations. ,, Commonly used precursors include ( N -[3-(Trimethoxy silyl)­propyl]- N , N , N -trimethylammonium chloride (TMAPS), 3-aminopropyl triethoxysilane (APTES), tetraethyl orthosilicate (TEOS), and calcium (Ca 2+ ) and magnesium (Mg 2+ ) ions. Various studies demonstrated that biomineral shells improve the mechanical properties ,, and enhance thermal , and biochemical stability , of DO-based assemblies. Furthermore, DO technology has provided new opportunities in the engineering of complex inorganic nanostructures with precise shapes and rich types of hybrid materials. …”
Section: Introductionmentioning
confidence: 99%